TEACHERS’ PERCEPTIONS OF SEX EDUCATION AND ITS EFFICIENCY IN PREVENTING SEXUAL ABUSE AMONG STUDENTS WITH LEARNING DIFFICULTIES (LD) - Celik, Pinar (Journal of Early Childhood Education (JECE), 2022)
The sex education of children with LD (learning difficulties) has been researched less than that of typically developing children, which shows that more research is needed on the issue of sex education in children with LD (Barnard-Brak et al., 2014; Grove et al., 2018). Because children with LD do not know what to do and how to protect themselves when they are exposed to sexual abuse, it is necessary to provide those who are vulnerable with sufficient education (Lumley et al., 1998; Blake, 2013). Examining the opinions of the people and teachers who are closest to these children and educate them will contribute to this field. Interviews with 5 teachers based in the UK who work with children with learning difficulties aged 4-19 were conducted in 2020/2021. This qualitative research provides an overview of sex education and protection from sexual harassment, with a focus on sex education programmes such as RSE (Relationships and Sex Education) in special education schools, emphasizing their importance and developing programmes especially for children with LD. There is a review of the relevant literature and a section explaining the methodological approach chosen. The findings and analysis of the themes that emerged as a result of the interviews with the teacher participants are discussed, and recommendations for best practice in schools are identified, along with directions for future research on a larger scale.